Dressing tools with controlled abrasive grain population for grinding aerospace materials - Spampinato, Alessio (2018)
In aerospace manufacturing, strict tolerances (i.e. <5 μm) and specific roughness (i.e. Ra<1 μm) of the machined surfaces are mandatory requirements, in order to obtain high performance of complex systems such as turbine engines. In this regard, the grinding operation plays a fundamental role in machining of aerospace components, such as fir-tree roots of turbine blades, characterised by complex profiles and employing heat resistant materials (e.g. nickel-based superalloy).